Transition policies for electromobility: comparative analysis between Brazil and France - Farias Justino da Silva, Isabela; Vasconcelos Valério, Bianca Maria; Silva Lucena, Sabrina Rayane (Latin American Journal of Energy Research, 2025)
This study provides a comprehensive analysis of the policy landscape for the transition from fossil fuel-based mobility to electric mobility in Brazil and France, highlighting public policies, economic incentives, and technological advances, considering how each of these countries has behaved in the new socio-environmental context. The results show that France has a more consolidated scenario, with a greater share of electric cars in the market, an extensive charging network, and greater financial incentives, thus stimulating the acceptance of light electric vehicles. Brazil, on the other hand, despite having a favorable energy matrix, still has limited policies, insufficient infrastructure, and high car prices, factors that hinder the expansion of this sector. It is concluded that, while France already stands out as a benchmark in electromobility, Brazil needs to overcome structural and economic challenges to ensure this progress.
Keywords: Electric mobility; Public policies; Energy transition; Electric vehicles.